Analisis Kinerja Struktur Bangunan Bertingkat Di Wilayah Gempa Indonesia Intensitas Tinggi Menggunakan Analisis Statis Nonlinier - Sri Fatma Reza; Reni Suryanita; Ismeddiyanto Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Indonesia is part of an area that is known for earthquake and volcano eruption activities. Because of this, one of the structural planning concept in Indonesia is by analyzing structure performance after earthquake activity. The purpose of this research is to identify performance and distribution of plastic hinge on structure storeyed buildings at Indonesia area with high intensity earthquake by using nonlinear static analysis method. Structure model is varied by height and number of floors, Model 1 is building with 5 floor, Model 2 is building with 10 floors, and Model 3 is building with 15 floors.Building is made from reinforced concrete with constant height of 4 meters. Building model receives earthquake load in the form of response spectrum of earthquake area with high ground accelaration (g). Earthquake area that is picked is at Banda Aceh with two soil condition (moderate soil and softsoil). Structure performance is decided by using ATC-40 code which is affected by target displacement. Method which is used to obtain target displacement is ATC-40 capacity spectrummethod and displacement coefficient FEMA 356. Analysis result shows performance level of all three models IO (Immediate Occupancy) are similar in moderate soil and soft soil condition.Keywords: moderate soil and soft soil condition, nonlinear static analysis, plastic hinge, response spectrum, structure performance, structure storeyed building.